Joanna Mary Boyce: a Pre-Raphaelite pilgrimage in Umbria (Altre Modernità, 2023)
From the middle of the 19th century, Umbria was a land of discovery for several Pre-Raphaelite women painters from England, who pictorially interpreted the 'enchantment' of the local landscape and culture. Their interest focuses on the most remote places in the region characterised by a spatial, cultural, and social isolation that, in their eyes, gave the Umbrian hill towns the physiognomy of perfectly preserved and living ancient communities. This is the case of the impressions gained by the painter Joanna Mary Boyce during her stay in Todi in 1857, as witnessed by several letters and a notebook of travel sketches that were fundamental for the realisation of one of her most successful paintings: The Departure - An Episode of the Child’s Crusade (1857-1861). The attention of the female artists-travellers (including Evelyn Pickering De Morgan and Marie Spartali Stillman) to the Umbrian landscape, to the art and history of small towns contributes to feeding the Pre-Raphaelite legend of 'enchanted' Umbria. This precise imagery, profoundly characterising and destined to adapt to the times or to be overturned by reaction in the Italian and European artistic culture of 20th century, is also summarised and discussed in the volume A Little Pilgrimage in Italy (1911) by Olave Muriel Potter.
Keywords: Pre-Raphaelites; traveling Artists; central Italy; travel Books; english Artist in Italy; female Artists